Deer Hunting : Misalignment, Debt Accumulation, and Desired Equilibrium Exchange Rates - Taylor, Mark (IMF Working Papers; Working Paper ;, 1993)
This paper deals with hysteresis in the desired equilibrium exchange rate (DEER) arising from misalignment. When the actual real exchange rate departs from its DEER value, current account realizations--and consequently, debt service obligations--will differ from those assumed in the initial DEER calculation, necessitating its recomputation. The paper derives a formal expression for this hysteresis effect in the DEER, studies the convergence properties of a system in which the evolution of actual exchange rates depends on the DEER and provides illustrative calculations of its historical significance. Finally, the paper derives and applies rules of thumb for computing the hysteresis effect when considering the rate of approach of an exchange rate to its DEER value.